2009
DOI: 10.1523/jneurosci.3952-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nicotinic Acetylcholine Receptor Subtype in Basal Forebrain Cholinergic Neurons with High Sensitivity to Amyloid Peptides

Abstract: Nicotinic acetylcholine receptors (nAChRs) containing ␣7 subunits are thought to assemble as homomers. ␣7-nAChR function has been implicated in learning and memory, and alterations of ␣7-nAChR have been found in patients with Alzheimer's disease (AD). Here we report findings consistent with a novel, naturally occurring nAChR subtype in rodent, basal forebrain cholinergic neurons. In these cells, ␣7 subunits are coexpressed, colocalize, and coassemble with ␤2 subunit(s). Compared with homomeric ␣7-nAChRs from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 49 publications
(74 reference statements)
8
162
2
3
Order By: Relevance
“…If b2 subunits are present in human adrenal chromaffin cell a3b4* nAChRs, they are likely to be restricted to the fifth or auxiliary position because no pharmacological evidence for an a3-b2 ligandbinding site was found. Additionally, b2 subunits may assemble with a7 subunits to form a7b2 nAChRs, which have recently been identified in rodent and human basal forebrain as well as mouse hippocampal interneurons (Liu et al, 2009b(Liu et al, , 2012Moretti et al, 2014).…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…If b2 subunits are present in human adrenal chromaffin cell a3b4* nAChRs, they are likely to be restricted to the fifth or auxiliary position because no pharmacological evidence for an a3-b2 ligandbinding site was found. Additionally, b2 subunits may assemble with a7 subunits to form a7b2 nAChRs, which have recently been identified in rodent and human basal forebrain as well as mouse hippocampal interneurons (Liu et al, 2009b(Liu et al, , 2012Moretti et al, 2014).…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…These receptors may have a presynaptic localisation where they are involved in the direct release of glutamate in the hippocampus and VTA, and of excitatory amino acid in the prefrontal cortex [92], or the indirect release of DA from striatum and prefrontal cortex, and noradrenaline from the hippocampus [93][94][95]) or a subtype has different biophysical and pharmacological properties from those of wild-type basal forebrain neurons, thus indicating that the subunits probably assemble to form a new subtype in the former [96].…”
Section: Homomeric and Heteromeric α7 Receptorsmentioning
confidence: 99%
“…A careful examination of subunit compositions of α7 receptors in bovine adrenal chromaffin cells supported the possibility of a small population of heteromeric α7 receptors expressed in chromaffin cells [48] . More recently, Liu et al reported the presence of heteromeric α7β2 receptors in rodent basal forebrain cholinergic neurons [23] ; moreover, these receptor are more sensitive than are homomeric receptors to functional blockade by oligomeric Aβ , which would implicate them in Alzheimer's disease. It will be important to determine if there are heteromeric α7* receptors in rat hippocampus and cerebral cortex; and if so, how these heteromeric α7 receptors contribute to the differences in binding profiles between homomeric α7 nAChRs in KXα7R1 cells and native α7* nAChRs.…”
Section: Channel Properties Of α7 Nachrs Expressed In the Kxα7r1 Cellsmentioning
confidence: 99%
“…The α7 nAChRs have been implicated in a wide range of physiological functions, including neurotransmitter release [15,16] , activation of second messengers, apoptosis and neuroprotection [17,18] . More recent evidence indicates that α7 nAChRs may be directly involved in learning and memory [19,20] , pathology of Alzheimer's disease [21][22][23] , and inflammation [24] . The advance in our understanding of the biological properties and roles of α7* nAChRs has suggested new therapeutic strategies and drug candidates targeting α7 nAChRs for treatment of CNS disorders, including Alzheimer's disease [25,26] .…”
Section: Introductionmentioning
confidence: 99%